Pharmacist-Led Pediatric Diarrhea Management: A Systematic Review of Knowledge and Recommendation Appropriateness - Ebtavanny, Tamara Gusti; Fitri, Salsabilah Aida; Suhartono, Suhartono; Hariadini, Ayuk Lawuningtyas (Pharmaceutical Journal of Indonesia, 2025)
Diarrhea remains a leading cause of morbidity and mortality among children, particularly in areas with inadequate sanitation. Community pharmacists often serve as the first point of care, making their role crucial in ensuring appropriate, guideline-based management of pediatric diarrhea. This systematic review aimed to evaluate pharmacists’ knowledge and the appropriateness of their recommendations for treating pediatric diarrhea. A systematic literature review was conducted using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) protocol. Searches were performed via Harzing’s Publish or Perish on Google Scholar, PubMed, and Crossref using keywords: "diarrhea" AND "pediatric" OR "children" AND "treatment" AND "pharmacist" AND "knowledge". Ten articles met the inclusion criteria. Among five studies assessing knowledge, three reported generally good pharmacist knowledge, while two showed significant improvements post-intervention (P < 0.001 and P < 0.01). Pharmacists demonstrated good understanding of ORS use, treatment options, and non-pharmacological advice. However, they showed limited ability to identify signs of dehydration. In terms of treatment recommendations, six of nine studies reported inappropriate use of antibiotics, with few pharmacists recommending WHO-recommended therapies (ORS and zinc). In contrast, five studies found that non-pharmacological advice was the primary approach. Three factors significantly influenced knowledge and appropriateness: patient assessment (P = 0.006), self-medication training (P < 0.0005), and year of graduation (P = 0.004). Pharmacists generally possess good knowledge in certain aspects of pediatric diarrhea management, but often make inappropriate treatment recommendations. Structured education and training are needed to improve clinical decision-making and adherence to treatment guidelines.